2015
DOI: 10.1139/cjfr-2014-0552
|View full text |Cite
|
Sign up to set email alerts
|

Economics of harvesting boreal uneven-aged mixed-species forests

Abstract: The subject of this study is the economics of harvesting boreal uneven-aged mixed-species forests consisting of Norway spruce (Picea abies (L.) Karst.), Scots pine (Pinus sylvestris L.), birch (Betula pendula Roth and B. pubescens Ehrh.), and other broadleaves. The analysis is based on an economic description of uneven-aged forestry, applying a size-structured model. The optimization problem is solved in its general dynamic form using gradient-based interior point methods. When volume yield is maximized, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 28 publications
1
50
0
Order By: Relevance
“…Thomson 1991;Knoke et al 2005;Rämö and Tahvonen 2015). Therefore, this research supports the view that the benefits of mixed forest management cover more than only intrinsic values and biodiversity.…”
Section: Ecosystemsupporting
confidence: 76%
“…Thomson 1991;Knoke et al 2005;Rämö and Tahvonen 2015). Therefore, this research supports the view that the benefits of mixed forest management cover more than only intrinsic values and biodiversity.…”
Section: Ecosystemsupporting
confidence: 76%
“…These studies (cf. Rämö and Tahvonen 2015) suggest the inclusion of multiple tree species in future studies on CCF with optimal harvest timing and on the optimal choice between the management regimes. In Tahvonen and Kallio (2006), it is shown that wood price stochasticity and risk aversion calls for diversifying the age structure in a multiple stand even-aged model.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible to maintain a continuous cover of plants [4][5][6][7][8]. A few investigations indicate that continuous-cover forestry has particular benefits [9][10][11][12][13][14][15][16][17]. As a special case of the continuous-cover process, a stationary system may appear.…”
Section: Introductionmentioning
confidence: 99%